Optimizing The Use of Social Media as a Source of Information and Communication - Muthi’ah; Tsuraya, Annisa Shofa; Sari, Hikma Patika; Lilaalamin, Dzulqarnain Rahmat; Hamidah, Nur (IJOCSE: Indonesian Journal of Community Services, 2023)
The ease of accessing information in this 4.0 reforamation era has become indispensable, because the high number of active social media users in Indonesia continues to soar. Publication in the mass media is very important, because all series of activities can be accessed very easily by users and will reflect good quality in the eyes of the community, this is the basis for the creation of official social media partners of English Education Department of UIN Alauddin Makassar. On the other hand, there are still obstacles when wanting to access information, both distance, time, and energy barriers. Especially for students, optimizing social media is a solution because it can make it easier to access and get information or news. This was welcomed by English Education partners and students in this service activity. With the existence of social media as a medium of communication and a means of obtaining information in the English Education Department, it can make it easier for users to find information and can find out the developments in the English Education study program. As for the method of implementing this service, there are several stages such as interview with partners, surveys of students, preparation, and socialization. It is hoped that the optimization of social media will continue to be improved to be applied to various other types of social media applications, so that the English Education Department of UIN Alauddin Makassar can be known by many people with a good image and this social media as a forum for making achievements.